A etnomatemática no espaço de uma feira agroecológica: (re)conhecendo saberes e fazeres locais - Antunes, Paulo Rafael (2021)
Based on the theoretical assumptions of the ethnomathematics program, we present an investigation carried out in the space of an agroecological fair, in the city of Foz do Iguaçu/PR. We describe the knowledge and practices of the fair marketers, identified in the cultural context of this space and in their traditional work practices, from the perspective of a teacher-researcher. We intend to recognize elements of the mathematical culture existing in this agroecological fair, experienced by its actors. That is, to recognize some of the local knowledge and practices, specific to that socioeconomic space and those people, thus contributing to a reflection on the mathematical constructions carried out by this socio-cultural group. For data collection, we conducted a field research which included observations of the practices carried out by the fair's marketers, photographic records of the fair and its products, as well as many informal conversations recorded in a research diary. Based on the rereading, interpretation and analysis of the collected data, we present this dissertation. As a result, we highlight the perception of a ethnomathematics, contextualized and proper to the fair's subjects, motivated by its natural, social and cultural environment, which is identified in each commercial transaction that occurs, in the choice of the season for planting, in the preparation of products and their derivatives, in the spatial organization of the fair, in currency conversions, own measurement systems, among others.